Pengkajian Penanganan Pemberian Air Irigasi di Petak Terisolir Ujung Saluran Irigasi pada Musim Kemarau - Supadi, Supadi (MEDIA KOMUNIKASI TEKNIK SIPIL, 2009)
Indonesia has two seasons namely rainy season and dry season. When dry season comes, farmers got the hardest hit by the limited amount of water, to where it becomes very valuable. There are two ways to solve the deficit of water during dry season. The first way is to carry out an appropriate water management, and the second one is to initiate the efficient use of water. There are other problem involving water irrigation distribution in areas that comprise several regencies, especially in down stream areas where shortage of supply of irrigation water happens. Thus, it is imperative to manage water resources and water irrigation distribution system. For example, farmer community has to hold a meeting to set a plan of water distribution. Distribution of irrigation water can be accurately determined using coefficient value of K. When K value is less than 0,50, distribution of irrigation water should be implemented using on-off (intermittent) system.Keywords: Dry season, Civilian, Farmers, Water managementPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3418[How to cite: Supadi (2009). Pengkajian Penanganan Pemberian Air Irigasi di Petak Terisolir Ujung Saluran Irigasi pada Musim Kemarau, Jurnal Media Komunikasi Teknik Sipil, 17 (1): 1-8]